Cerebrovascular complications of hematopoetic stem cell transplantation in patients with hematologic malignancies - Alexey Yu. Polushin; Iaroslav B. Skiba; Evgeny A. Bakin; Maria D. Vladovskaya; Victoria A. Yakovleva; Ivan S. Moiseev; Stanislav N. Yanishevskiy; Igor A. Voznyuk; Alexander D. Kulagin (Анналы клинической и экспериментальной неврологии, 2023)
Introduction. Modern transplantation and biological therapy methods are associated with a wide range of adverse events and complications. Incidence and variety of neurological complications mostly depend on myelo- and immunosuppression severity and duration as well as on donor's and recipient's characteristics. The most frequent complications involving the nervous system include neurotoxic reactions, infections, autoimmune and lymphoproliferative diseases, and dysmetabolic conditions as well as cerebrovascular complications that potentially affect transplantation outcomes.